Evaluasi Model Kearsipan dalam Upaya Pengelolaan Arsip di Universitas Islam Negeri Maulana Malik Ibrahim Malang - Sholahuddin, Moh.; Roziki, Khaﬁd; Nurdiana, Laily Shintya (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
Evaluation of the university archiving model is important, relevant and needs to be studied to increase the eﬀectiveness and eﬃciency of document and record management in an organization, including universities. The paper presents an evaluation of the archival model in terms of implementation, impacts, and provides recommendations for the development of a better archival model evaluation. This research uses a qualitative method by placing the State Islamic University (UIN) Maulana Malik Ibrahim Malang as the center of study. Data were collected by observation, interview, and documentation. The results showed that the evaluation of the archive management model of UIN Maulana Malik Ibrahim Malang was not fully in accordance with Law number 43 of 2009 in the aspects of archive creation, storage, and destruction. The discrepancy is due to the absence of an archival model evaluation framework that accommodates archive retention schedules (JRA) and classiﬁcation systems and dynamic archive access security (SKKAAD) as an integrated part of its archive management instruments. This study is the ﬁrst of its kind to evaluate an internal archival model within a State Islamic Universities in Indonesia. As an integral part, the archival model evaluation framework is designed to implement adequate archival management in religious universities in Indonesia. This research serves as an initial study, indicating the need for more comprehensive empirical studies based on these ﬁndings to be developed progressively in the future.